Nursing ergonomics: Strategies for preventing occupational diseases and promoting worker health (Research, Society and Development, 2025)
Ergonomics in nursing is a key component in promoting occupational health and reducing physical, cognitive, and organizational burdens that affect professional performance and patient safety. This study aimed to analyze the available evidence on ergonomic risks, associated occupational disorders, and preventive strategies for nursing professionals in healthcare settings. A narrative review with qualitative and quantitative characteristics was conducted between August and November 2025, using DeCS/MeSH descriptors combined with boolean operators and structured according to adapted phases of PRISMA 2020. Searches were performed in SciELO, PubMed, and Google Scholar, as well as in international guidelines and Brazilian regulatory standards, resulting in 40 documents included in the final synthesis. The findings revealed a high prevalence of work-related musculoskeletal disorders, physical and mental fatigue, occupational stress, and burnout, strongly associated with manual handling, awkward postures, high cognitive demands, extended work shifts, and organizational shortcomings. The most effective strategies identified included safe patient handling and mobility (SPHM) programs, “no-lift” policies, assistive technologies for mobilization, participatory ergonomics, workplace redesign, and continuous education. The study concludes that integrating these measures with NR-17 and NR-32 standards is essential to promote safer, healthier, and more sustainable work environments, contributing to professional well-being, retention of nursing staff, and the strengthening of high-quality patient care.